Psychosocial Evaluation Results of Children and Adolescents Followed within the Scope of Health Measure - Kul, Müslüm; Dağ, Pelin; Akdağ, Berhan; Canoğulları Kul, Gülçin (The Bulletin of Legal Medicine, 2023)
Objective: This study aimed to examine the clinical and sociodemographic characteristics of children and adolescents whom juvenile courts have given health measures. Methods: The data of 351 cases that were followed up and treated in the Child and Adolescent Mental Health and Diseases Outpatient Clinic of Mersin City Training and Research Hospital between March 2017 and June 2022 were retrospectively analyzed. Results: The mean age of the cases was 12.71±3.61, and the majority (66.1%) were girls. The family’s inadequacy in care was the most common reason for health measure decisions (35.3%). 54.7% of children and adolescents belonged to broken families. While the rate of having at least one psychiatric diagnosis was 63.2%, the most common diagnosis was anxiety disorder, with 23.9%. Nearly half of the cases (46.7%) were not followed up regularly within the scope of health measures. Conclusion: The frequency of health measure decisions for children and adolescents is increasing. This study exhibited the high rates of psychopathology and family problems in children with health measure decisions. A holistic approach that includes the family and social environment should be developed in these cases’ follow-up and treatment processes.